Purveyors of fine halos: III. chemical abundance analysis of a potential [omega]Cen associate - Koch-Hansen, Andreas; Hansen, Camilla Juul; Lombardo, Linda; Bonifacio, Piercarlo; Hanke, Michael; Caffau, Elisabetta (Astronomy and astrophysics, 2021)
Globular clusters (GCs) are important donors to the build-up of the Milky Way (MW) stellar halo, having contributed at the ten percent level over the Galactic history. Stars that originated from the second generation of dissolved or dissolving clusters can be readily identified via distinct light-element signatures such as enhanced N and Na and simultaneously depleted C and O abundances. In this paper we present an extensive chemical abundance analysis of the halo star J110842, which was previously kinematically associated with the massive MW GC ω Centauri (ωCen), and we discuss viable scenarios from escape to encounter. Based on a high-resolution, high signal-to-noise spectrum of this star using the UVES spectrograph, we were able to measure 33 species of 31 elements across all nucleosynthetic channels. The star’s low metallicity of [Fe II/H] = −2.10 ± 0.02(stat.) ± 0.07(sys.) dex places it in the lower sixth percentile of ωCen’s metallicity distribution. We find that all of the heavier-element abundances, from α- and Fe-peak elements to neutron-capture elements are closely compatible with ωCen’s broad abundance distribution. However, given the major overlap of this object’s abundances with the bulk of all of the MW components, this does not allow for a clear-cut distinction of the star’s origin. In contrast, our measurements of an enhancement in CN and its position on the Na-strong locus of the Na-O anticorrelation render it conceivable that it originally formed as a second-generation GC star, lending support to a former association of this halo star with the massive GC ωCen.